PENGEMBANGAN BUKU DIGITAL BERBASIS KEARIFAN LOKAL JAWA MENGGUNAKAN APLIKASI CANVA PADA MATA PELAJARAN PENDIDKAN PANCASILA MATERI KERAGAMAN BUDAYA DI KELAS IV SDN DEPOK 01 - Assyifa, Zahra; Satriyani, Febrianti Yuli (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This research aims to develop digital book media based on local Javanese wisdom using the Canva application on Pancasila education subjects on cultural diversity. This research uses the Research and Development or RnD method. The results of this research are based on validation which obtained an average value of 89.33%. With 88% of language experts, 94% of material experts and 86% of media experts. Judging from the calculation of students' response questionnaires, they got a total score of 1406 points out of 1755 points or 80.11%. The results of student scores experienced a significant increase of 12%, namely from the average percentage of pretest scores before using learning media of 71% where only 12 students out of 27 students succeeded in passing the KKM and the average percentage of student scores during the posttest or after using the product was 83% where students experienced an increase in scores.